Optimizing the Quality of Services, Products and Digital Promotions for Restaurants and Restaurants on Satisfaction and Interest Guests Revisit the City Entrance Area Parapat Tourism in Simalungun Regency - Hanafi, Mhd Hirsan; Siregar, Mhd Daud; Hutabarat, Setia Putra (International Journal of Economics and Management, 2024)
The Parapat area also highlights culinary diversity with unique eateries and restaurants as well as cafes offering various culinary experiences. Gumarang Restaurant presents a rich Minang culinary experience, inviting guests to enjoy delicious and traditional dishes. Meanwhile, Sehat Restaurant brings uniqueness to each of its dishes with creative touches, creating an unforgettable dining experience for consumers. On the other hand, the Kantor Pos Parapat Cafe emphasizes a relaxed atmosphere combined with practical service, offering comfort to guests seeking an enjoyable dining experience.This research aims to optimize the quality of service, products, and digital promotion in similar eateries and restaurants, focusing on their impact on consumer satisfaction and interest in revisiting the area. This study is of a quantitative nature. The population identified in this research consists of business owners, consumers, and employees located in the Entrance Area of Parapat Tourist City in Simalungun Regency. The sampling technique used is purposive sampling with a sample size of 97 respondents. The data is then analyzed using the partial least squares method using SmartPLS 4.0 software. The results of this study indicate that service quality has a positive and significant effect on consumer satisfaction, product quality has a positive and significant effect on consumer satisfaction, digital promotion of eateries and restaurants has a positive and significant effect on consumer satisfaction, consumer satisfaction has a positive and significant effect on the intention of consumers to revisit. The consumer satisfaction variable is able to mediate the influence of service quality, product quality, and digital promotion on the intention of consumers to revisit.